38-[60-7×8+(a:3+4)]:5=35
Răspunsuri la întrebare
Răspuns de
13
38 - [ 60 - 7 × 8 + ( a : 3 + 4 ) ] : 5 = 35
38 - [ 60 - 56 + ( a : 3 + 4 ) ] : 5 = 35
38 - [ 4 + ( a : 3 + 4 ) ] : 5 = 35
[ 4 + ( a : 3 + 4 ) ] : 5 = 38 - 35
[ 4 + ( a : 3 + 4 ) ] : 5 = 3
[ 4 + ( a : 3 + 4 ) ] = 3 × 5
[ 4 + ( a : 3 + 4 ) ] = 15
a : 3 + 4 = 15 - 4
a : 3 + 4 = 11
a : 3 = 11 - 4
a : 3 = 7
a = 7 × 3
a = 21
38 - [ 60 - 56 + ( a : 3 + 4 ) ] : 5 = 35
38 - [ 4 + ( a : 3 + 4 ) ] : 5 = 35
[ 4 + ( a : 3 + 4 ) ] : 5 = 38 - 35
[ 4 + ( a : 3 + 4 ) ] : 5 = 3
[ 4 + ( a : 3 + 4 ) ] = 3 × 5
[ 4 + ( a : 3 + 4 ) ] = 15
a : 3 + 4 = 15 - 4
a : 3 + 4 = 11
a : 3 = 11 - 4
a : 3 = 7
a = 7 × 3
a = 21
Alte întrebări interesante
Chimie,
8 ani în urmă
Limba română,
8 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă